Spatial and temporal characterization of standard duration-maximum precipitation over Black Sea Region in Turkey - Aksu, Hakan; Cetin, Mahmut; Aksoy, Hafzullah; Yaldiz, Sait Genar; Yildirim, Isilsu; Keklik, Gulsah (Natural hazards (Dordrecht), 2022)
This study characterises the spatial and temporal behaviours of maximum precipitation over the Black Sea Region in northern Turkey. Maximum precipitation data of 14 standard durations changing from 5 min to 24 h were used from 21 meteorological stations in the region with record lengths ranging from 25 to 71 years. In line with the objective of the study, tests for the detection of outliers, homogeneity, and trend were applied in order to reveal the structural characteristics of the data set. Tests detected no outlier, and the homogeneity analysis found only three stations fully homogeneous, all others being inhomogeneous. Change points identified in the data set by the homogeneity tests were linked to the local characteristics of meteorological stations. Trend analysis revealed that slightly more than half of the meteorological stations are exposed to a positive trend in the maximum precipitation of one standard duration at a minimum. The main conclusion is that maximum precipitation is subject to change over the Black Sea Region in Turkey.